Hydrogels promote periodontal regeneration - Sun, Huiying; Luan, Jiayi; Dong, Shujun (Frontiers in Bioengineering and Biotechnology, 2024)
Periodontal defects involve the damage and loss of periodontal tissue, primarily caused by periodontitis. This inflammatory disease, resulting from various factors, can lead to irreversible harm to the tissues supporting the teeth if not treated effectively, potentially resulting in tooth loss or loosening. Such outcomes significantly impact a patient’s facial appearance and their ability to eat and speak. Current clinical treatments for periodontitis, including surgery, root planing, and various types of curettage, as well as local antibiotic injections, aim to mitigate symptoms and halt disease progression. However, these methods fall short of fully restoring the original structure and functionality of the affected tissue, due to the complex and deep structure of periodontal pockets and the intricate nature of the supporting tissue. To overcome these limitations, numerous biomaterials have been explored for periodontal tissue regeneration, with hydrogels being particularly noteworthy. Hydrogels are favored in research for their exceptional absorption capacity, biodegradability, and tunable mechanical properties. They have shown promise as barrier membranes, scaffolds, carriers for cell transplantation and drug delivery systems in periodontal regeneration therapy. The review concludes by discussing the ongoing challenges and future prospects for hydrogel applications in periodontal treatment.